AMALAN BIMBINGAN PENSYARAH TERHADAP PENINGKATAN KUALITI GURU PELATIH: SATU KAJIAN KES - NURULHIDAYAH LUCY ABDULLAH (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2021)
The main principle in coaching practices is referred to self-guided learning that train an individual how to learn. Therefore, this study aims to identify the coaching practices and how to improve the quality of trainee teachers’ teaching during practicum. The main focus is given to the pedagogical development of trainee teachers which is the yardstick for the quality of teaching of trainee teachers. Qualitative data collection was conducted on two trainee teachers. Findings show that the coaching practices of guidance given by lecturers to trainee teachers should be continued, appreciated and nurtured during practicum because it can help trainee teachers identify problems, find solutions and solve problems. It also simplifies the responsibility of trainee teachers and improves the quality of their teaching.